Caring for patients with advanced breast cancer: The experiences of Zambian nurses - Johanna Elizabeth Maree; Jennipher Kombe Mulonda (Elsevier, 2017)
Objective: The objective of this study was to describe the experiences of Zambian nurses caring for women with advanced breast cancer. Methods: We used a qualitative descriptive design and purposive sampling. Seventeen in-depth interviews were conducted with registered nurses practicing in the Cancer Diseases Hospital and the University Teaching Hospital, Lusaka, Zambia, and analyzed using thematic analyses. Results: Two themes emerged from the data - caring for women with advanced breast cancer is challenging and the good outweighs the bad. The majority of the participants agreed that caring for women with advanced breast cancer and witnessing their suffering were challenging. Not having formal education and training in oncology nursing was disempowering, and one of the various frustrations participants experienced. The work environment, learning opportunities, positive patient outcomes, and the opportunity to establish good nurse-patient experiences were positive experiences. Conclusions: Although negative experiences seemed to be overwhelming, participants reported some meaningful experiences while caring for women with advanced breast cancer. The lack of formal oncology nursing education and training was a major factor contributing to their negative experiences and perceived as the key to rendering the quality of care patients deserved. Ways to fulfill the educational needs of nurses should be explored and instituted, and nurses should be remunerated according to their levels of practice.